Development of Group Guidance Model with Transactional Approach to Improving the Quality of Interpersonal Communication Based on Minangkabau Culture - Yusri, Fadhilla; Pratiwi, Siska; Usman, Hanifah (JURNAL KONSELING GUSJIGANG, 2024)
This study aims to develop a social conflict prevention model through group guidance with a transactional approach to improve the quality of interpersonal communication based on Minangkabau culture. This development research uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Purposive sampling technique was used to select 230 high school students as subjects in the study. The product validity test was carried out by 9 competent experts. The product practicality test was carried out by 9 guidance and counseling teachers. The data were analyzed descriptively and inferentially with the Kendall’s coefficient test statistic. The research produced a social conflict prevention model through group guidance with a valid and practical transactional approach to improve the quality of interpersonal communication based on Minangkabau culture. The research concludes that the social conflict prevention model through group guidance with a transactional approach can be used to improve the quality of interpersonal communication based on Minangkabau culture.